2016
DOI: 10.1037/adb0000192
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management is effective in promoting abstinence and retention in treatment among crack cocaine users in Brazil: A randomized controlled trial.

Abstract: BACKGROUND Crack cocaine dependence has become a severe public health problem in Brazil, and current psychosocial approaches to this problem have shown little or no effectiveness. Although contingency management is among the most effective behavioral treatments for substance use disorders, it has never been applied in the treatment of crack cocaine-dependent individuals in Brazil. AIMS To evaluate the efficacy of incorporating contingency management into standard outpatient treatment for crack cocaine depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
3
37
0
4
Order By: Relevance
“…In the United Kingdom, it is included in the National Institute for Health and Clinical Excellence guidelines (NICE, 2007). It has also been successfully applied in other European countries as well as Brazil and China (Chen et al, 2013; Etter & Schmid 2016; Hser et al, 2011; Miguel et al, 2016; Petitjean et al, 2014; Secades-Villa, Garcia-Rodriguez, & Fernandez-Hermida 2015; Wang et al, 2014). …”
Section: Efficacy Of CMmentioning
confidence: 99%
“…In the United Kingdom, it is included in the National Institute for Health and Clinical Excellence guidelines (NICE, 2007). It has also been successfully applied in other European countries as well as Brazil and China (Chen et al, 2013; Etter & Schmid 2016; Hser et al, 2011; Miguel et al, 2016; Petitjean et al, 2014; Secades-Villa, Garcia-Rodriguez, & Fernandez-Hermida 2015; Wang et al, 2014). …”
Section: Efficacy Of CMmentioning
confidence: 99%
“…The present study utilized data collected in a randomized clinical trial designed to evaluate the effect of CM on crack cocaine use, the duration of abstinence from crack cocaine, treatment attendance, and treatment retention in a population of treatment-seeking crack cocaine-dependent individuals in the city of Sao Paulo (Miguel et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Vouchers could be exchanged for any goods available in the surrounding community, with the exceptions of tobacco products and alcohol. A full description of the methodology employed is available elsewhere (Miguel et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group conducted the first randomized clinical trial (RCT) of CM for the treatment of CUD in Brazil (Miguel et al, 2016). We observed that, in comparison with the participants receiving usual care (control condition), those treated with CM had a lower frequency of cocaine use, achieved longer periods of continuous cocaine abstinence, and were more likely to be retained until the end of the treatment.…”
Section: Introductionmentioning
confidence: 99%